2020
DOI: 10.3390/cells9030781
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation Induces Retinal Müller Cell Proliferation and Their Progenitor Cell Potential

Abstract: Non-invasive electrical stimulation (ES) is increasingly applied to improve vision in untreatable eye conditions, such as retinitis pigmentosa and age-related macular degeneration. Our previous study suggested that ES promoted retinal function and the proliferation of progenitor-like glial cells in mice with inherited photoreceptor degeneration; however, the underlying mechanism remains obscure. Müller cells (MCs) are thought to be dormant residential progenitor cells that possess a high potential for retinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 56 publications
2
37
0
Order By: Relevance
“…Concordantly, TES positively modulated the expression of the brain-derived neurotrophic factor (BDNF) and ciliary neurotrophic factor (CNTF) in the retina, which prolonged the survival of photoreceptors and preserved retinal functions in mouse models of photoreceptor degeneration induced by light or N-methyl-N-nitrosourea [ 36 , 46 ]. Studies using Müller cell cultures also demonstrated that TES could stimulate the production of IGF-1, BDNF, and CNTF, resulting in significant induction of Müller cell proliferation [ 37 , 38 , 39 , 40 ]. The induction of these growth factors by electrical stimulation was suggested to be dependent on the activation of L-type voltage-dependent calcium channels (L-VDCCs), as blocking L-VDCCs downregulated IGF-1 and BDNF, as well as attenuating Müller cell proliferation [ 37 , 38 , 40 ].…”
Section: Mechanisms Of Action Of Tesmentioning
confidence: 99%
See 2 more Smart Citations
“…Concordantly, TES positively modulated the expression of the brain-derived neurotrophic factor (BDNF) and ciliary neurotrophic factor (CNTF) in the retina, which prolonged the survival of photoreceptors and preserved retinal functions in mouse models of photoreceptor degeneration induced by light or N-methyl-N-nitrosourea [ 36 , 46 ]. Studies using Müller cell cultures also demonstrated that TES could stimulate the production of IGF-1, BDNF, and CNTF, resulting in significant induction of Müller cell proliferation [ 37 , 38 , 39 , 40 ]. The induction of these growth factors by electrical stimulation was suggested to be dependent on the activation of L-type voltage-dependent calcium channels (L-VDCCs), as blocking L-VDCCs downregulated IGF-1 and BDNF, as well as attenuating Müller cell proliferation [ 37 , 38 , 40 ].…”
Section: Mechanisms Of Action Of Tesmentioning
confidence: 99%
“…Studies using Müller cell cultures also demonstrated that TES could stimulate the production of IGF-1, BDNF, and CNTF, resulting in significant induction of Müller cell proliferation [ 37 , 38 , 39 , 40 ]. The induction of these growth factors by electrical stimulation was suggested to be dependent on the activation of L-type voltage-dependent calcium channels (L-VDCCs), as blocking L-VDCCs downregulated IGF-1 and BDNF, as well as attenuating Müller cell proliferation [ 37 , 38 , 40 ].…”
Section: Mechanisms Of Action Of Tesmentioning
confidence: 99%
See 1 more Smart Citation
“…The human retina differs significantly from that of lower order animals, and human PSC-derived organoids therefore provide a better platform to study EF-induced therapeutic effects on the human retina. In vitro , primary eye-derived retinal glial cells (Müller Glia) were found to respond to electrical stimulation with increased proliferation and expression of cell fate determinant genes ( Enayati et al, 2020 ). Specifically, this was linked to the action of Calcium signalling ( Enayati et al, 2020 ).…”
Section: Enhancing Organoid Cultures With Bioelectricitymentioning
confidence: 99%
“…In vitro , primary eye-derived retinal glial cells (Müller Glia) were found to respond to electrical stimulation with increased proliferation and expression of cell fate determinant genes ( Enayati et al, 2020 ). Specifically, this was linked to the action of Calcium signalling ( Enayati et al, 2020 ). Several studies have also reported a regenerative response of the output neurons of the retina, the retinal ganglion cells, in response to biomimetic stimulation ( Fu et al, 2015 ; Gordon, 2016 ).…”
Section: Enhancing Organoid Cultures With Bioelectricitymentioning
confidence: 99%